2015
DOI: 10.2147/ijn.s86313
|View full text |Cite
|
Sign up to set email alerts
|

Probing insulin bioactivity in oral nanoparticles produced by ultrasonication-assisted emulsification/internal gelation

Abstract: Alginate–dextran sulfate-based particles obtained by emulsification/internal gelation technology can be considered suitable carriers for oral insulin delivery. A rational study focused on the emulsification and particle recovery steps was developed in order to reduce particles to the nanosize range while keeping insulin bioactivity. There was a decrease in size when ultrasonication was used during emulsification, which was more pronounced when a cosurfactant was added. Ultrasonication add-on after particle rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 78 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…Another study was conducted to evaluate the particle size of insulin nanoparticles synthesized via emulsification/internal gelation. Similar trend of results was observed where the reduction of particle size (442 nm to 317 nm) was enabled by applying ultrasonication for 15 min, after which the size started to expand [ 161 ]. To enable a marked reduction of particle size, it was envisaged that ultrasound sonication brought about emulsion droplet breakdown by means of cavitation phenomena, yet lengthening this process time rendered the coalescence of emulsion droplets as a result of elevating the medium temperature and hence larger particle size [ 162 ].…”
Section: Factors Influencing Alginate Nanoparticles’ Characteristisupporting
confidence: 81%
See 1 more Smart Citation
“…Another study was conducted to evaluate the particle size of insulin nanoparticles synthesized via emulsification/internal gelation. Similar trend of results was observed where the reduction of particle size (442 nm to 317 nm) was enabled by applying ultrasonication for 15 min, after which the size started to expand [ 161 ]. To enable a marked reduction of particle size, it was envisaged that ultrasound sonication brought about emulsion droplet breakdown by means of cavitation phenomena, yet lengthening this process time rendered the coalescence of emulsion droplets as a result of elevating the medium temperature and hence larger particle size [ 162 ].…”
Section: Factors Influencing Alginate Nanoparticles’ Characteristisupporting
confidence: 81%
“…As shown in Table 6 , alginate-chitosan nanoparticles with small size and high encapsulation efficiency were produced at halfway between pKa of these species (pH ~ 4.8). Besides, intensifying of electrostatic interactions is represented by zeta potential values, in which high negative values indicate an absence of free cationic groups on the surface of nanoparticles, that correlated to high encapsulation efficiency and drug loading propensity [ 161 ].…”
Section: Factors Influencing Alginate Nanoparticles’ Characteristimentioning
confidence: 99%
“…This three-hour insulin release would result in its availability close to the absorption site, which constitutes an excellent benefit for oral insulin bioavailability [ 19 ]. CD, the technique to monitor the integrity of insulin against harsh conditions [ 18 ], as seen in Figure 1 , showed that the spectrum of unprocessed standard insulin (I) in PBS at pH 7.4 has bands with two minima at approximately 209 and 224 nm, indicating the presence of a significant α-helix structure with some β–sheets. Insulin released from nanoparticles (II) showed a similar spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan stabilizes alginate-based hydrogels during the formulation of nanoparticles and enhances insulin absorption through the paracellular route [ 17 ]. Chitosan coating is essential to strengthen the alginate/dextran sulfate core [ 18 ] and to incorporate other polyanionic biopolymers that increase insulin stability against GI enzymes and pH and to modulate insulin release in the GI tract [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it does not mean that this tech-nology is perfect, since it may cause some consumer feel nausea. Thus, if researchers want to use this technology as food application, some specific corrigent is necessary [49][50][51][52][53][54][55] .…”
Section: Other Methodsmentioning
confidence: 99%